Arguing through literature - Ferster, Judith (McGraw-Hill Higher Education, 2005)
Includes bibliographical references and index; 4 parts: An introduction to reading and writing; the Elements of Literature; argument, research and literature: conversations among different kinds of writing; an anthology of readings; Quỹ Châu Á